Avances y tendencias del trabajo social en los años 80 en España - Miguel Angel Oliver; Virgínia Alves Carrara; Rosana Matos –Silveira (Eleuthera)
This paper presents the preliminary results of the research Fundamentals of Social Work: professional tendency in the process of democratization in Spain, which seeks to understand the situation of the profession in the 1980s. Using a critical socio-historical methodological theoretical approach bibliographical-documentary sources are analyzed, highlighting the contents of the proceedings of the IV State Congress of Social Workers in Valladolid in 1980, and interviews are conducted with people who participated in different movements and organizations of the time. With the Spanish Constitution (SC) of 1978 and the incorporation of Spain into the European Economic Community (EEC), the profession will seek new perspectives from an approach to the debates that were taking place in Europe and which will end up having a significant impact on Spanish Social Work.